KARAKTERISTIK παραπεσόντας DALAM SURAT IBRANI (STUDI EKSEGESE IBRANI 6:4-6) - Heri Lim (Sekolah Tinggi Teologi Injili Jakarta, 2022)
This paper attempts to explain the characteristics of παραπεσόντας. The interpretation of Hebrews 6:4-6 is one of the topics in New Testament biblical discussion which deals with the dangers of apostasy. The difficulty faced in this discussion is how to harmonize the description in Heb 6:4–5 with the statements in Heb 6:6 about they who have fallen away and no longer to be restored to repentance. This article is explained by looking at the sentence structure, lexicon, grammar, context, as well as the opinion of the New Testament scholars.Keywords: Apostasy, Warning, Hebrews, Participle Abstrak: Tulisan ini mencoba menjelaskan karakteristik παραπεσόντας. Penafsiran Ibrani 6:4-6 adalah salah satu topik dalam diskusi Alkitab Perjanjian Baru yang berhubungan dengan bahaya kemurtadan. Kesulitan yang dihadapi dalam pembahasan ini adalah bagaimana menyelaraskan uraian dalam Ibr 6:4–5 dengan pernyataan dalam Ibr 6:6 tentang mereka yang telah murtad dan tidak lagi akan dipulihkan kepada pertobatan. Artikel ini dijelaskan dengan melihat struktur kalimat, leksikon, tata bahasa, konteks, serta pendapat para ahli Perjanjian Baru.. Kata kunci: Kemurtadan, Peringatan, Ibrani, Partisip.